The Efficacy of Seminal Vesicles Extract Administration on Percentage of Estrus and Pregnancy on Local Goat - Syafruddin S; Tongku Nizwan Siregar; Herrialfian H; T Armansyah; Arman Sayuti; Roslizawaty R (Jurnal Kedokteran Hewan, 2010)
The aim of this research was to determine the percentage of estrus, performance of estrus, and percentage of pregnancy in local goat which synchronized with seminal vesicles extract. The seminal vesicles used in this research were collected from the waste of Banda Aceh slaughter house. The goats were allotted into 2 groups. Goats in group were injected with 0.5 ml PGF2á intramuscularly, and goats in group II were injected with 5 ml seminal vesicles extract intrauterine. The injection was done twice with the interval of 11 days. The goats which perform estrus sign are mated naturally once in every observation. Pregnancy diagnosing was done using chemical urine method 2 months after mating. The estrus  percentage  and  pregnancy data were analyzed with chi-square  and  the estrus  performance (onset  and  estrus duration) were analyzed  using  student T test. The estrus onset of group I and II were 29.33±4.62 and 24.00±0.00 hours (P0.05). Estrus duration of group I and II were 26.67+4.62 and 20.00+11.97 hours respectively (P0.05). The  estrus percentage  of  group  I and  II did not  show  any significant differences (P0.05), those are 60.0 and 40.0%  respectively,  whereas   the percentage of estrus  from  both  groups were 100.0 %.